The association between visceral fat indices and diabetic peripheral neuropathy in type 2 diabetes mellitus: A retrospective cross-sectional study - Aydogdu, Nesibe; Karakeci, Emel Sabaz (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2026)
Objectives: The research investigates how type 2 diabetes mellitus (T2DM) patients with diabetic peripheral neuropathy (DPN) their visceral fat indices, which include visceral adiposity index, lipid accumulation product, and atherogenic plasma index (AIP). Patients and methods: The retrospective study analyzed 562 T2DM patients (324 females, 238 males; mean age: 64 +/- 13.3 range, 56 to 72 years) between January 2022 and December 2024. Participants were divided into two groups based on their electromyography (EMG) results and Leeds Assessment of Neuropathic Symptoms and Signs pain scale scores (a score of 12 or higher indicated neuropathy). Electromyography-positive patients (n=213) were compared with EMG-negative patients (n=349) for their anthropometric data, results, and visceral fat measurements. Independent factors that predicted DPN were sought to be identified. Results: The EMG-positive patients showed higher values for body mass index, visceral adiposity index, lipid accumulation product, AIP, as well as triglycerides and hemoglobin A1c levels, compared to EMG-negative patients (p<0.001 and p<0.01). The logistic analysis revealed that hemoglobin levels (odds ratio =0.83, 95% confidence interval 0.74-0.94), hemoglobin A1c levels, waist circumference, and AIP served as independent risk factors for DPN. Conclusion: The findings show that visceral fat indices serve as effective biomarkers in identifying T2DM patients at high risk of DPN. The combination of these indices with glycemic control monitoring could improve DPN prevention methods. Future research to conduct bigger prospective studies to confirm these findings and understand the intricate links between lipid metabolism, and DPN.
Keywords: Atherogenic plasma index; diabetes mellitus; diabetic peripheral neuropathy; lipid accumulation product; visceral adiposity index.